2012
DOI: 10.1016/j.neuron.2012.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Mutant PrP Suppresses Glutamatergic Neurotransmission in Cerebellar Granule Neurons by Impairing Membrane Delivery of VGCC α2δ-1 Subunit

Abstract: SummaryHow mutant prion protein (PrP) leads to neurological dysfunction in genetic prion diseases is unknown. Tg(PG14) mice synthesize a misfolded mutant PrP which is partially retained in the neuronal endoplasmic reticulum (ER). As these mice age, they develop ataxia and massive degeneration of cerebellar granule neurons (CGNs). Here, we report that motor behavioral deficits in Tg(PG14) mice emerge before neurodegeneration and are associated with defective glutamate exocytosis from granule neurons due to impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 66 publications
7
99
0
Order By: Relevance
“…α 2 δ2-L1040P is unable to reproduce the most common effects of α 2 δ2-WT: an increase in whole cell amplitude and acceleration of inactivation 22 23. Since α 2 δ increases hVGCC currents both via effects on channel gating and surface expression,6 24 25 the α 2 δ2-L1040P mutant appears deficient in performing one or both of these essential functions. Prolonged channel opening during depolarisation, associated with slow inactivation, could partly underlie the epileptic phenotype; low current amplitude would add to the development of an aberrant calcium signalling pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α 2 δ2-L1040P is unable to reproduce the most common effects of α 2 δ2-WT: an increase in whole cell amplitude and acceleration of inactivation 22 23. Since α 2 δ increases hVGCC currents both via effects on channel gating and surface expression,6 24 25 the α 2 δ2-L1040P mutant appears deficient in performing one or both of these essential functions. Prolonged channel opening during depolarisation, associated with slow inactivation, could partly underlie the epileptic phenotype; low current amplitude would add to the development of an aberrant calcium signalling pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged channel opening during depolarisation, associated with slow inactivation, could partly underlie the epileptic phenotype; low current amplitude would add to the development of an aberrant calcium signalling pattern. Furthermore, lack or dysfunction of α 2 δ2 is expected to affect synaptogenesis and spatio-temporal calcium signalling,13 25 aggravating the pathology. Our clinical data and the results of the electrophysiological studies are in agreement with the spike wave seizures reported in mice carrying a spontaneous mutation in α 2 δ2 (ducky alleles) associated with an aberrant α 2 δ2 protein 26–29.…”
Section: Resultsmentioning
confidence: 99%
“…Also, PrP C and a mutant PrP C version that is linked to a genetic prion disease have been shown to co-immunoprecipitate with the auxiliary subunit α2δ-1 of VGCCs in transgenic mice [78]. Mutant PrP C affected α2δ-1 trafficking and function at the synapses.…”
Section: Possible Functions For Prpc Are Suggested By Interaction Parmentioning
confidence: 99%
“…A major gap exists in our understanding of how conversion of PrP C to PrP Sc causes neuronal dysfunction and death. Various mechanisms have been proposed including synaptic impairment (Senatore et al, 2012), ubiquitin-proteasome system (UPS) dysfunction (Kristiansen et al, 2007), endoplasmic reticulum (ER) stress (Hetz et al, 2003;Rane et al, 2008), toxicity due to the presence of PrP species in the cytosol (Chakrabarti and Hegde, 2009;Kristiansen et al, 2005;Ma et al, 2002), and unfolded protein response induction and translational arrest (Moreno et al, 2012). To assess the contribution of these mechanisms to prion-induced toxicity, it is essential to know the exact cellular trafficking pathways of PrP Sc .…”
Section: Introductionmentioning
confidence: 99%